Analisis Kesulitan Menulis Permulaan pada Siswa Kelas 1 UPTD SDN Banyuajuh 2 - Rizqy Atthoriqoh; Tyasmiarni Citrawari; Fadlillah Fadlillah; Nilamsari Damayanti Fajrin; Ira Dyan Puspita (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
Beginning writing is a skill that is taught to students at the initial stage, namely in class I. This research is motivated by the difficulties faced by students in the Indonesian language subject of learning to start writing in class I. This research aims to describe the difficulties of learning to start writing and identify factors -factors causing difficulties in learning to write at the beginning of class I at UPTD SDN Banyuajuh 2. This research uses descriptive qualitative methods. The subjects of this research were 4 class I students with difficulty in beginning writing. Data collection techniques used were observation, interviews and documentation. Based on research results, several writing difficulties experienced by class I students include: not being able to write their full name or nickname, not being able to write the letters of the alphabet correctly, not being able to copy words and not being able to write on the right lines. Then the factors that influence initial writing difficulties are internal factors including students' low fine motor skills, students' low visual abilities, study habits and low learning interest and motivation. Meanwhile, external factors for students include a lack of parental attention and guidance towards students.